Accumulation of Plastic Debris Trapped in the Riparian Vegetation of the Bedog River, Indonesia, Based on the Complexity of the Plant Structure - Inggita Utami; Nobuaki Tanaka (Department of Biology, Faculty of Science and Technology, Syarif Hidayatullah State Islami, 2026)
Plastic accumulation not only degrades water quality but also impacts riparian vegetation. Vegetation plays a key role in trapping plastic debris; however, the influence of plant structure and environmental factors on this process remains poorly understood. This study evaluates the trapping capacity of riparian vegetation along the Bedog River, Yogyakarta, and identifies the key factors controlling plastic accumulation. A riparian target map was first developed using satellite and drone imagery to classify land use and land cover. Trapping capacity was estimated based on vegetation structural parameters and validated through field surveys conducted across 20 plots, 3 m² each, distributed along the upstream-to-downstream gradient during both the dry and wet seasons. Plastic cover per unit area and environmental variables were analyzed using statistical approaches. The results show that bamboo exhibits the highest trapping capacity and plastic accumulation, followed by grass and arboreal vegetation, highlighting the importance of structural density and rigidity. Plastic cover was significantly higher during the dry season, indicating that riparian zones act as temporary storage under low-flow conditions. Environmental factors further influenced accumulation, with higher retention observed in low-elevation and low-slope areas, while flow velocity showed seasonal effects. These findings emphasize that vegetation structure and hydrodynamic conditions govern plastic trapping, positioning riparian zones as critical targets for plastic pollution management in tropical river systems.